2010
DOI: 10.1074/mcp.m110.001370
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Diversification of the Anguimorpha Lizard Venom System

Abstract: Because of significant differences in anatomy of the venom delivery system and distant phylogenetic relatedness, it had been long assumed that the venom systems of snakes and helodermatid lizards were independently evolved (1-3). However, both lineages were recently revealed to be members of a clade (Toxicofera) that also included several lineages of other lizards recently shown to be venomous (4, 5). In contrast to the hypothesis of independent origins, this new perspective revealed that lizard and snake veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
97
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 60 publications
7
97
0
3
Order By: Relevance
“…Both databases were interrogated using representative venom sequences utilised by Fry et al [10][11][12]29 . Sequence searches were undertaken for 12 toxin families identified as basal to the Toxicofera (AVIT, cystatin, cysteine-rich secretory protein, CVF, crotamine, hyaluronidase, kallikrein, lectin, natriuretic peptides, NGF, veficolin and vespryn) [10][11][12] . Contigs exhibiting a BLAST e-value cut-off of 1e − 05 were retained.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both databases were interrogated using representative venom sequences utilised by Fry et al [10][11][12]29 . Sequence searches were undertaken for 12 toxin families identified as basal to the Toxicofera (AVIT, cystatin, cysteine-rich secretory protein, CVF, crotamine, hyaluronidase, kallikrein, lectin, natriuretic peptides, NGF, veficolin and vespryn) [10][11][12] . Contigs exhibiting a BLAST e-value cut-off of 1e − 05 were retained.…”
Section: Methodsmentioning
confidence: 99%
“…Contig hits were incorporated into DNA data sets of toxin (derived from members of the Toxicofera) and non-toxin (sampled from outside groups -that is, non-reptilian species) sequences used in the analyses of Fry et al [10][11][12]29 . All sequences were obtained from GenBank -GI accession numbers are displayed in the resulting gene trees (Figs 2-5; Supplementary Figs S2-S6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent lack of specialization of the venom system within the Iguania is likely because of the fact that most species are insectivorous or vegetarian; however, we have shown that toxin genes continue to be expressed by the oral glands of these lizards (18). In the snakes and Anguimorpha lizards, by contrast, the venom system has been extensively diversified (18,20,22,24,29). In the anguimorph lizards, specialization of the mandibular gland was favored, whereas in snakes it was the maxillary gland that became most specialized; in both lineages highly derived forms exist, including encapsulated glands.…”
mentioning
confidence: 93%
“…(Fig. 1A) (2,7,(17)(18)(19)(20)(21)(22)(23)(24). Although Toxicofera, which consists of three lineages (Anguimorpha lizards, Iguania lizards, and Serpentes) is well established as a monophyletic clade within the squamate reptiles (18,25); phylogenetic studies based on nuclear genes have thus far failed to resolve the relative relationships of the snake/iguanian/anguimorph trichotomy [cf (2,25,26).…”
mentioning
confidence: 99%